Penerapan Lean Manufacturing pada Lini Produksi Hinge AFT dan Hinge FWD - 10070220016, Ahmad Hidayat Naqsabandi; Nita P. A. Hidayat; Chaznin R. Muhammad (Bandung Conference Series: Industrial Engineering Science, 2025)
Abstract. PT. Dirgantara Indonesia (PT. DI) is a manufacturing company that produces the first aircraft in Indonesia. PT. DI implements a strategy to respond to the Engineering to Order (ETO) and Make to Order (MTO) markets. Based on the observation results, there are several activities that cause waste, namely defects, transportation and waiting time. The waste that occurs can result in companies taking longer to complete the products they produce. Therefore, Lean Manufacturing is used as an effort to reduce waste. The tools that will be used in this study are SIPOC Diagram, Value Stream Mapping (VSM), Pareto Diagram, Causal Diagram, Failure Mode and Effect Analysis (FMEA), and 7 Waste Questionnaire. The results obtained from the stage of identifying waste using the 7 Waste Questionnaire are that there are four types of the highest waste, namely defect, transportation, waiting time and motion. The waste is then identified to find out the factors that cause waste using the Cause and Effect Diagram, so that it can be used as input to calculate the Risk Priority Number (RPN) using FMEA. Based on the recommendations, the proposed improvements include designing a maintenance checklist, designing visual work standardization using a monitoring form, adding tools in the form of a reach truck, and redesigning the production layout. If the proposed improvement recommendations are implemented, it will result in a total production lead time that decreases from 409.89 minutes to 348.74 minutes. In addition, the Process Cycle Efficiency (PCE) value increased from 53.71% to 63.13%. Abstrak. PT. Dirgantara Indonesia (PT. DI) merupakan perusahaan manufaktur yang memproduksi pesawat terbang pertama di Indonesia. PT. DI menerapkan strategi merespon pasar Engineering to Order (ETO) dan Make to Order (MTO). Berdasarkan hasil observasi terdapat beberapa aktivitas yang menyebabkan pemborosan, yaitu defect, transportation dan waiting time. Pemborosan yang terjadi dapat mengakibatkan perusahaan memerlukan waktu yang lebih lama untuk menyelesaikan produk yang dihasilkannya. Oleh karena itu, Lean Manufacturing digunakan sebagai upaya untuk mengurangi pemborosan. Tools yang akan digunakan pada penelitian ini adalah Diagram SIPOC, Value Stream Mapping (VSM), Diagram Pareto, Diagram Sebab Akibat, Failure Mode and Effect Analysis (FMEA), dan Kuesioner 7 Waste. Hasil yang diperoleh dari tahapan mengidentifikasi pemborosan dengan menggunakan Kuesioner 7 Waste yaitu terdapat empat jenis pemborosan tertinggi yaitu defect, transportation, waiting time dan motion. Pemborosan tersebut kemudian diidentifikasi untuk mengetahui faktor penyebab terjadinya pemborosan dengan menggunakan Diagram Sebab Akibat, sehingga dapat dijadikan input untuk menghitung Risk Priority Number (RPN) dengan menggunakan FMEA. Berdasarkan rekomendasi, maka usulan perbaikan berupa perancangan maintenance checklist, perancangan standarisasi kerja secara visual dengan menggunakan form monitoring, penambahan alat bantu berupa reach truck, dan perancangan ulang layout produksi. Apabila usulan rekomendasi perbaikan diimplementasikan, maka akan menghasilkan total production lead time yang menurun dari 409,89 menit menjadi 348,74 menit. Selain itu, nilai Process Cycle Efficiency (PCE) mengalami peningkatan dari 53,71% menjadi 63,13%.